Brains That Are out of Tune but in Time - Hyde, Krista L.; Peretz, Isabelle (Psychological Science, 2004)
It is estimated that about 4% of the general population may have amusia (or tone deafness). Congenital amusia is a lifelong disability for processing music despite normal intellectual, memory, and language skills. Here we present evidence that the disorder stems from a deficit in fine-grained pitch perception. Amusic and control adults were presented with monotonic and isochronous sequences of five tones (i.e., constant pitch and intertone interval). They were required to detect when the fourth tone was displaced in pitch or time. All amusic participants were impaired in detecting the pitch changes, and showed no sign of improvement with practice. In contrast, they detected time changes as well as control adults and exhibited similar improvements with practice. Thus, the degraded pitch perception seen in the amusic individuals cannot be ascribed to nonspecific problems with the task or to poor hearing in general. Rather, the data point to the presence of a congenital neural anomaly that selectively impairs pitch processing.